Returns to Education in Azerbaijan : Some New Estimates - Garcia Moreno, Vicente; Patrinos, Harry Anthony (Taylor and Francis, 2021)
This article estimates private and social returns to investment in education in Azerbaijan, using the 2015 Azerbaijan Monitoring Survey for Social Welfare. The private rate of return to education is 6 percent; this is the first estimate of returns to schooling in Azerbaijan since 1995. The returns to schooling are 6 percent for men and 8 percent for women, even controlling for selection. In addition, the article estimates the returns for higher education; for this level, the rate of return is 9 percent. Finally, using the full discount method, the private rate of return for tertiary education is 9 percent, and the social rate of return is 8 percent. One policy implication is to reexamine the funding of higher education and its expansion.